Building the Hyksos' Vassals: Some Thoughts on the Definition of the Hyksos Subordination Practices - Flammini, Roxana Claudia (2015)
In Egyptology, the subordinates of the Hyksos are commonly defined as vassals, often without giving a definition of the concept and as a consequence, the complexity that subordination practices might acquire is overlooked. In this paper, I present a revision of the origin and meaning of the concept of vassal, the underlying paradigms that sustain it, and discuss the scarce evidence as to reconstruct the subordination practices carried out by the Hyksos in Egypt.